DETERMINAN YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI INDONESIA PERIODE 1970-2020 - Jumaedi, M.; Chaidir, Taufiq; Firmansyah, M. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023DO - 10.24843/EEB.2023.v12.i04.p05, 2023)
This study aims to investigated the determinants of economic growth in Indonesia for the period 1970 to 2020. This study uses the Error Correction Model (ECM) to analyze the effects from the determinants of economic growth in short-run and long-run. The data for this study uses time series data since 1970-2020 taken from the World Bank website. The variables used in this study are Economic Growth as dependent variable, and then International Trade, Foreign Direct Investment (FDI) and Inflation as Variables independent. Empirical test results using Error Correction Model (ECM) found that (1) international trade has a significant and negative effect on economic growth in the long run, while in the short run international trade has no effect on economic growth in Indonesia (2) Foreign Direct Investment (FDI) has a significant and positive effect on economic growth both in the long-run and short-run, and (3) Inflation has a significant and negative effect both in the long-run and short-run on economic growth in Indoensia.